Pengembangan Sistem Pendidikan Agama Islam Pada Perguruan Tinggi Umum (Suatu Kajian Inter, Multi dan Transdisipliner) - Nanang Budianto (FALASIFA : Jurnal Studi Keislaman, 2016)
Continuity of education is inseparable from coordination and intense communication in the process of applying Subjects Islamic Education between departments in order to avoid throwing the responsibility, in addition to the compulsory subjects in universities, especially Penguruan Public Higher in the lecture does not simply pass on the material, but how students are able to understand, appreciate and practice the teachings of the Islamic religion in total in everyday life. Based on the position of Islamic education is a subject which equip learners form the basic ability of understanding, appreciation and experience of basic values of humanity, as a creature of God, as individuals, members of families, communities, citizens and as part of nature. Islamic Education in Public Higher Education (PTU) is useful for helping students terbinanya faithful and devoted to Allah SWT.Key Word: Development, Public Higher Education curricula